IMPROVING PATIENT SAFETY AND HOSPITAL SERVICE QUALITY THROUGH ELECTRONIC MEDICAL RECORD: A SYSTEMATIC REVIEW - Muhammad Firdaus; Amal Chalik Sjaaf (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Examines properly implementation of Electronic Medical Records (EMR) which associated with workflows, policies and health services in enhancing patient safety. The electronic medical records have benefit to the patients due to the efficiency in the healthcare process. Therefore, the aim of this study was to examine the literatures on patients safety reporting based on electronic system review and assess the implementation. Methods: Systematic review with Prisma at the literature published between 2010 – 2019 using three large database: Proquest, Oxford Academic Journals, and Scopus. The eligible articles in this review should show an effect of patient’ safety, and product quality in hospital in correlation on using EMR. It must include some effect on medication error, prescribing error, error in the use of EMR that potentially endanger patient safety. Results:The most important function of EMR implementation is to improve patient safety in hospital and to reduce the cost. EMR reduce excess cost of Hospital Acquired Condition (HAC) by 16%, reduce death due to HAC by 34%. Doctor and nurses believe that the quality of patient data would be better by using EMR as their daily routines. Conclusion: EMR can improve patient safety due to some skills in technology. Thus, it would not harm to the patients safety. However, the implementation of EMR requires the human skill resources in using technologies, computer and programs.